Effects of flux application and melting parameters in investment casting of pure aluminium by in-situ melting technique - Saleh, Aslinda (2018)
Investment cast aluminium suffers porosity defect attributed to the complex combination of various factors including melt quality, casting process parameter and pouring technique. Even though, melt treatment and controlled of the process parameter have promising result, however turbulence developed during pouring of molten aluminium increasing the formation of porosity as a result of the entrainment of the surface oxide (Al2O3) film known as bifilm. Currently, turbulence free filling system was applied in casting process using tilt casting, bottom filling integrated with low pressure and also in-situ casting or in-situ melting techniques to address the porosity problem. However, in-situ melting technique has not been studied to reduce the porosity of the investment cast aluminium due to the oxidation of the granular aluminium occurs during heating hinders the complete melting of the granules. This research develops a procedure for investment casting of aluminium granules of 99.4% purity by in-situ melting technique. The aluminium granules were filled in ceramic moulds and heated at four different temperatures of 700, 750, 800 and 850oC for 30 and 60 min in a high temperature muffle furnace in ambient. As the heating temperature and duration were increased, the aluminium granules incompletely melt and produced a casting, however the granules agglomerate and replicate the shape of the ceramic mould. The aluminium granules oxidised during heating, encapsulated by a layer of complex oxides composed of stable [α-Al2O3], metastable [γ-Al2O3] and hydroxides. The thickness of the oxide layer formed on the surface of the air-heated granules increased as the heating temperature and duration were increased. The aluminium granules then were heated at the temperature of 850oC for 30 min in argon environment at the flow rate of argon gas 0.5, 2.5 and 5 l/min to reduce the oxidation of the aluminium granules. The thickness of the oxide layer formed on the argon-heated granule (5 l/min) was reduced by 60%, but failed to produce a casting. NaCl-KCl flux was applied, which was mixed and sprinkled on the aluminium granules at the Al:Flux ratio of 1:0.2, 1:0.25 and 1:0.33 and heated at the temperature of 850oC for 30 min to break the oxide layer that encapsulate the granules during heating. At the Al:Flux ratio of 1:0.33, 99% of the aluminium granules were successfully melted and produced a casting. The granules began melting at the temperature range 657.2 to 658.4oC and completely melted in 16 min with final melting temperature between 660.1 and 660.6oC. The average porosity level of the casting was 1.22%, which is lower than the investment cast aluminium produced by current pouring technique (2.48%). The low porosity level was attributed to micro-intergranular porosity present in the casting due to volume shrinkage. Investment casting of aluminium granules by in-situ melting technique with application of NaCl-KCl flux at the Al:Flux ratio of 1:0.33 mixed and sprinkled on the granules heated at the temperature of 850oC for 30 min producing low porosity aluminium casting.